HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PASIEN PASCA STROKE - Nurhalizah, Desy; Yulianto, Andri; Tiara (Literasi Intelektual, 2024)
Background: Post-stroke patients often experience a decline in quality of life due to physical, psychological, social, and economic limitations. Muscle weakness, mobility difficulties, and inability to perform daily activities reduce independence, making patients highly dependent on family support during recovery. Adequate family support can enhance motivation, confidence, and adaptability, while lack of support may lead to depression, helplessness, and poor quality of life. Many post-stroke patients still do not receive optimal family support, resulting in persistently low quality of life. Objective: This study aimed to analyze the relationship between family support and the quality of life of post-stroke patients in the working area of the Ambarawa Health Center, Pringsewu Regency. Methods: This quantitative study used an analytical cross-sectional design. The population consisted of 33 post-stroke patients selected using a total sampling technique. Data were collected using family support (30 items) and quality of life (25 items) questionnaires and analyzed using univariate and bivariate analyses with the Chi-Square test. Results: Among 17 respondents with good family support, 21 (88.2%) had good quality of life, while 12 of 16 respondents (68.8%) with poor family support had low quality of life. The Chi-Square test showed p = 0.000 (< 0.05), indicating a significant relationship between family support and quality of life. Conclusion: Family support plays a crucial role in improving post-stroke patients’ quality of life. The stronger the family support, the better the quality of life across physical, psychological, social, and economic aspects.